Stress, resilience and cardiovascular disease risk among African-American women: Results from the Women’s Health Initiative - Felix, Ashley S. (Circ Cardiovasc Qual Outcomes, 2019)
BACKGROUND: Empirical data on the link between stress and cardiovascular (CVD) risk among African-American women is limited. We examined associations of stressful life events and social strain with incident CVD among African-American women and tested for effect modification by resilience. METHODS AND RESULTS: Our analysis included 10,785 African-American women enrolled in the Women’s Health Initiative Observational Study and Clinical Trials cohort. Participants were followed for CVD for up to 23 years (mean, 12.5). Multivariable Cox regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for associations between stress-related exposures and incident CVD. We included interactions between follow-up time (age) and stressful life events due to evidence of non-proportional hazards. Effect modification by resilience was examined in the sub-cohort of 2,765 women with resilience and stressful life events measures. Higher stressful life events was associated with incident CVD at ages 55 (HR for highest vs lowest quartile=1.80, 95% CI=1.27–2.54) and 65 (HR for highest vs lowest quartile=1.40, 95% CI=1.16–1.68), but not at older ages. Adjustment for CVD risk factors attenuated these associations. Similar associations were observed for social strain. In the sub-cohort of women with updated stressful life events and resilience measures, higher stressful life events was associated with incident CVD in multivariable-adjusted models (HR=1.61, 95% CI=1.04–2.51). Resilience did not modify this association nor was resilience independently associated with incident CVD. CONCLUSIONS: In this cohort of older African-American women, recent reports of stressful life events were related to incident CVD. Resilience was unrelated to incident CVD. CLINICAL TRIALS REGISTRATION INFORMATION: URL: www.clinicaltrials.gov. Unique identifier: NCT00000611.